Measuring adolescent health literacy in Taiwan: validation of the health literacy assessment scale for adolescents - An-Kuo Chou; Chun-Hua Liao; Duan-Rung Chen (BMC Public Health, 2023)
Abstract Background This study aimed to validate the Chinese version of the Health Literacy Assessment Scale for Adolescents (HAS-A) and conduct a comparative analysis of adolescent health literacy between Taiwan and other countries. Methods The Chinese version of the HAS-A was completed by 2,312 adolescents in the fifth and sixth grades of a primary school. Psychometric properties were examined using consistent internal reliability and confirmatory factor analysis. These assessments were compared with the results from different regions to explore health literacy inequality. Results Construct validity was good, and internal consistency was acceptable. The scale, particularly regarding communication health literacy, was associated with parents’ socioeconomic status, and family income had a more significant impact on children’s health literacy than community income. Health literacy disparities appear in different countries, with Taiwan exhibiting the lowest level of communication health literacy. Conclusion The results indicate that the HAS-A is a valuable tool for assessing the health literacy of 10–11-year-old adolescents and can uncover health literacy inequality among different regions.